2016
DOI: 10.3892/or.2016.4718
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-603 functions as an oncogene by suppressing BRCC2 protein translation in osteosarcoma

Abstract: The present study was conducted to investigate the expression of miR-603 in osteosarcoma cells, and the effect of miR-603 on the biological behavior and expression of breast cancer cell 2 (BRCC2) in osteosarcoma cells. In the present study, qRT-PCR was used to measure the levels of miRNA and mRNA. The results showed that miR-603 was significantly upregulated in human osteosarcoma tissues and cell lines. MTT and colony formation assays were employed to evaluate the role of miR-603 in the regulation of osteosarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…2B ) and we propose it is attempting to regulate of E2F1 in a negatively correlated fashion which may contribute to nodular SGC less aggressive behaviour (Supplementary Fig. S3 ) 24 , 25 . A miRNA-target gene network of the proposed regulatory interactions seen in nodular SGC is shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 93%
“…2B ) and we propose it is attempting to regulate of E2F1 in a negatively correlated fashion which may contribute to nodular SGC less aggressive behaviour (Supplementary Fig. S3 ) 24 , 25 . A miRNA-target gene network of the proposed regulatory interactions seen in nodular SGC is shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Examination of the relationships between miRNAs and human osteosarcoma possibly provide a new orientation for the diagnosis and therapy of osteosarcoma. In previous studies, partial miRNAs were reported to inhibit osteosarcoma tumorigenicity and to suppress cell proliferation; and partially were reported to promote osteosarcoma cell proliferation and induce cell survival ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA binding may lead to mRNA degradation or translational repression, depending on the extent of complementarity with each target region (42)(43)(44) (Figure 1). miRNAs have also been shown to regulate genes transcriptionally via interacting with lncRNAs, leading to the up-or down-regulation of target genes (45)(46)(47).…”
Section: Mirnas Regulating Thyroid Carcinogenesismentioning
confidence: 99%